The World Bank's Evolutionary Approach to Mining Sector Reform - McMahon, Gary (World Bank, Washington, DC, 2014)
In this report, in addition to aggregate results, six brief case studies are used to highlight the impact of Bank supported mining sector reform on various indicators at different links of the value chain. These include: the impacts on investment; production and employment in Argentina; institutional capacity building in Papua New Guinea; production and fiscal revenues in Tanzania; community and regional development in Madagascar; mining sector reform and sustainable development in Mongolia; and mining and resource corridors in Liberia. The reforms of the 1990s and early 2000s, which focused on increasing investment and building regulatory capacity, have often had spectacular results with respect to investment and good results with respect to institution building. The work on increasing the efficiency and transparency of fiscal regimes has also achieved significant success, although it is still too early to make a final assessment. While the mining sector-specific aspects of the management and allocation of fiscal revenues are still in early days, there do seem to have been important impacts on poverty reduction and sustainable development in a number of countries that have undergone mining reform, although there has been an insufficient passage of time to make definitive judgments.